Threshold F-policy and N-policy for multi-component machining system with warm standbys - Kamlesh Kumar; Madhu Jain (Journal of Industrial Engineering International, 2013)
This study is concerned with threshold F-policy and N-policy for controlling the arrivals and service in the queueing scenario of a machining system, having active and redundant components. For both F-policy and N-policy models, the queue size distributions are determined by the recursive method. Various performance measures, namely the average number of failed units in the system, probability that the server is busy or idle in the system, etc., are established using the queue size distribution.
Keywords: 650; Machining systems; F-policy; N-policy; Start-up time; Warm standbys; Recursive method; Queue size